If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + -3i)(-5 + i) = 0 Multiply (2 + -3i) * (-5 + i) (2(-5 + i) + -3i * (-5 + i)) = 0 ((-5 * 2 + i * 2) + -3i * (-5 + i)) = 0 ((-10 + 2i) + -3i * (-5 + i)) = 0 (-10 + 2i + (-5 * -3i + i * -3i)) = 0 (-10 + 2i + (15i + -3i2)) = 0 Combine like terms: 2i + 15i = 17i (-10 + 17i + -3i2) = 0 Solving -10 + 17i + -3i2 = 0 Solving for variable 'i'. Factor a trinomial. (-5 + i)(2 + -3i) = 0Subproblem 1
Set the factor '(-5 + i)' equal to zero and attempt to solve: Simplifying -5 + i = 0 Solving -5 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + i = 0 + 5 Combine like terms: -5 + 5 = 0 0 + i = 0 + 5 i = 0 + 5 Combine like terms: 0 + 5 = 5 i = 5 Simplifying i = 5Subproblem 2
Set the factor '(2 + -3i)' equal to zero and attempt to solve: Simplifying 2 + -3i = 0 Solving 2 + -3i = 0 Move all terms containing i to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3i = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3i = 0 + -2 -3i = 0 + -2 Combine like terms: 0 + -2 = -2 -3i = -2 Divide each side by '-3'. i = 0.6666666667 Simplifying i = 0.6666666667Solution
i = {5, 0.6666666667}
| 13-5x=-7x+7 | | 2x-2.4=5.5 | | (5-2i)(3+7i)= | | 2(x+1)=x-11 | | 5y+9=6 | | 100/3.14 | | 3(x+4)=5.2 | | x+t=2(2x-x)+6 | | 2/3-2/5-5/6 | | -2a+b=10 | | (D^2+D-6)y=0 | | 1/2x24=y | | x+8-x+3= | | y-5/8=-6(x-3) | | 8+3+x+x= | | 7x-9=-6[x+1]-16 | | M(3)=5x-2 | | y^2+30=64+8x | | X+8+x+3= | | (3x+2y)=51 | | 6(x+2)=6(x+2) | | 8x-25=-1 | | 7y-1=4y+2 | | c-1.8=1.34 | | 4x-2=6-2x | | 2(x-5)=x+5 | | 3x-2x=90+10 | | g(x)=10x-70 | | -18=-9b | | (x^2-5x-14)(4x+28)=0 | | R=2t^2-87t+90 | | 4x-1=5+6[x-3] |